Hematological and lipid profile changes in sea-level natives after exposure to 3550-m altitude for 8 months - Siques, P.; Brito, J.; Leon-Velarde, F.; Barrios, L.; Jose De La Cruz, J.; Lopez, V.; Herruzo, R. (High Altitude Medicine & Biology, 2007)
The aim of this epidemiological study was to determinate the effects on hematological and lipid profile in a young group of newcomers to altitude after being exposed chronically for 8 months to 3550 m (n = 50), age 17.8 ± 0.7; and not overweight, BMI 22.9 ± 0.5). Readings taken at altitude on day 1 and on month 8 were hematocrit (Hct, %), hemoglobin (Hb, g/dL), SaO2, total leukocyte and subset count (mm3, %), and lipid profile (mg/dL). The same measurements were taken in a comparative group (CG) at sea level (SL). At altitude, elevations of Hct (44.6 ± 0.4; 51.2 ± 0.4) and Hb (15.5 ± 0.1; 17.3 ± 0.1) were seen (p < 0.001) and none with Hb = 21 g/dL. No correlation was observed between Hb and SaO2, r = 0.11, p > 0.05. Total leukocyte count showed no changes (6037 ± 74; 6002 ± 43), but a relative neutropenia (55.2 + -1.5; 50.6 + -1.3) and lymphocytosis (34.2 + 1; 42.4 + 1, p < 0.001) between periods were found and also when compared to SL. Also, an inverse relationship between SaO2 and total leukocytes on month 8 (r = 0.46; r2 = 0.204), suggesting a probable representation of a hypoxia effect. Total cholesterol (153.8 ± 4.5; 157.3 ± 5.1; p, ns) showed no changes, but a mild decrease of LDL-cholesterol (88.4 ± 3.3; 81.0 ± 3.9; p < 0.05), and a rise in triglycerides (121.6 ± 10.9; 178.8 ± 11.7; p < 0.001) was found. Changes observed in leukocytes subset count and triglycerides could suggest a contributory role of hypoxic conditions, raising some future epidemiological concerns regarding immune system and fatty acid behaviour at altitude.